Two-stage robust optimization for nodal invulnerability enhancement of power grids - Zhang, Xueyang; Huang, Shengjun; Li, Qingxia; Wang, Rui; Zhang, Tao; Guo, Bo (International journal of electrical power & energy systems, 2024)
Due to the large-scale integration of renewable energy and inevitable disturbing events (including natural disasters and deliberate attacks), the invulnerability of power grids is facing a great challenge, thus the security criterion is demanded to upgrade from N−1 to N−k. However, with the increasing of k and the expanding of network scale, resource consumption of network expansion shows an exponential explosion. Therefore, it is necessary to improve the invulnerability of power grids from a new perspective. In this paper, the definition of nodal N−k security criterion is proposed, which divides buses into different security levels based on realistic demand, and decouples the security analysis from the system level to individual nodes. A two-stage robust optimization model is established, cooperating with the nodal N−k security criterion, the load demand of critical buses could be guaranteed. Moreover, the proposed discrepant upgrade scheme is flexible and has strong generalization performance, where enhanced buses and security levels can be selected independently based on the preferences of decision-makers. The effectiveness and efficiency of the proposal have been demonstrated in 5 cases, i.e., the IEEE 9-bus, 24-bus, 57-bus, 118-bus systems and an actual test system in India. •The definition of nodal N−k security criterion is proposed.•A defender–attacker–defender (DAD) model cooperating with the criterion is established.•A gradual and progressive enhancement framework is provided.